Vascular endothelial growth factor genetic variability and coronary artery disease in Brazilian population - Biselli, Patrícia Matos; Guerzoni, Alexandre Rodrigues; de Godoy, Moacir Fernandes; Pavarino-Bertelli, Érika Cristina; Goloni-Bertollo, Eny Maria (Heart and vessels, 2008)
Atherosclerosis results from a complex interaction between environment and genetic risk factors. The gene encoding vascular endothelial growth factor (VEGF) is associated with differential protein expression and has been investigated in coronary artery disease (CAD) studies. Based on this, we aimed at determining if patients with CAD are affected by polymorphisms (−2 578, −1 154, and 936) in the VEGF gene, and also if these polymorphisms are associated with the number of diseased vessels and degree of arterial obstruction. The case group was formed by 175 Caucasian patients with angiographically confirmed CAD, and the control group involved 108 Caucasian patients with normal coronary angiograms. Polymerase chain reaction (PCR) was used for genotyping. Allele frequencies for VEGF −2 578A, −1 154A, and 936T were 0.46, 0.38, and 0.14 in cases and 0.49, 0.30, and 0.13 in control subjects. Allele and genotype distribution did not significantly differ between groups. A higher frequency of the VEGF −2 578AA genotype was observed in the group with three vessel disease ( P = 0.008). No association between the VEGF −2 578, −1 154, and 936 polymorphisms and degree of arterial obstruction was observed. The frequency of carriers of two copies of the haplotype AG (−2 578/−1 154) were higher in the group with three-vessel disease ( P = 0.05). In summary, our report shows that the VEGF −2 578 polymorphism has an influence on CAD severity, possibly because of a reduced VEGF expression, suggesting a protective effect of VEGF in atherosclerosis.